Psychosocial impact of serological diagnosis of herpes simplex virus type 2: a qualitative assessment. Issue 4 (5th August 2003) - Melville, J; Sniffen, S; Crosby, R; Salazar, L; Whittington, W; Dithmer-Schreck, D; DiClemente, R; Wald, A
Abstract : Objectives: To assess the emotional and psychosocial responses to a serological diagnosis of HSV-2 infection in individuals without previous history of genital herpes. Methods: 24 individuals who had a positive HSV-2 serology by western blot and no clinical history of disease were recruited from four clinics (sexually transmitted disease, maternal and infant care, family medicine, and virology research) over a 10 month period. In-depth qualitative interviews were conducted to elicit an individual's responses to the HSV-2 diagnosis. Results: Three categories of themes were identified from the interviews. Short term emotional responses included surprise, denial, confusion, distress, sadness, disappointment, and relief to know. Short term psychosocial responses included fear of telling sex partners, anger at the source partner, guilt about acquiring or transmitting, and concern about transmitting to a child. Perceived ongoing responses included fear of telling future partners, concern about transmitting to a sex partner, feeling sexually undesirable, feeling socially stigmatised, feeling like "damaged goods, " sex avoidance due to social responsibility, fear of transmitting to a newborn, and relationship concerns relating to the diagnosis. Conclusions: Individuals exhibit strong emotional and psychosocial responses to a serological diagnosis of HSV-2 infection. Many of the negative responses may be time limited and influenced by factors that are potentially amenable to counselling.